Teaching and learning assessment: an empirical study at Advanced Technology Training Center (ADTEC) Malaysia - Selamat, Asri; Zaidi, Mohd Taufik Syazeli; Muhamad Hanafi, Nurfirdawati; Jumintono, Jumintono (Auricle Global Society of Education & Research, 2021)
Along with the rapid growth of science and technology, the country is forced to provide educational services that can be early to be observed by the public, including non-formal educational institutions such as the Advanced Technology Training Center (ADTEC) in Malaysia. This study was conducted toward lecturers in industrial training institutions in order for them to meet the assessment practices in education. The respondents consisted of 45 lecturers in ADTEC Batu Pahat, which is one of the industrial training institutes located in Batu Pahat, Johor. A questionnaire was developed as an instrument for data collection. Data were analysed using the Statistical Package for Social Science (SPSS) version 11.5. The findings show that ADTEC lecturers have a high level of knowledge about educational assessment. Besides, there are eight (8) forms of assessment applied by lecturers ADTEC Batu Pahat. The results of the study also found that the lecturers ADTEC Batu Pahat perform test plans based on the assessment procedure. With the perfect and industrial equipment combined with the latest methods of teaching and good learning and at the same time evaluated by an effective’s education evaluation system, ADTEC mission to produce competitive workers will be achieved. The study is useful for non-formal educational institutions in all Malaysian country to evaluate and improve their role in all days.